Municipal Development Strategy as an Instrument of Local Economic Development Policy - Sienkiewicz, Mariusz Wiktor (Socialiniai tyrimai, 2014)
The main objective of this paper is to determine the importance of local development strategies for formulating and implementing local economic development policies by local authorities. In particular, an attempt is made to answer the question of whether local authorities properly and effectively use public management tools (i.e. a development strategy) to promote economic development in their area. Furthermore, the aim of this article is to analyse instruments for supporting economic development, which can be potentially used by local governments in Poland.